NMR Metabolomic Analysis of Fecal Water from Subjects on a Vegetarian Diet - Rafter, Joseph James; Verpoorte, Robert; Karlsson, Pernilla Christina; Pettersson, Jenny; Choi, Young Hae; Bohlin, Lars (Biological & Pharmaceutical Bulletin, 2008)
A vegetarian diet rich in phytochemicals may prevent colon carcinogenesis by affecting biochemical processes in the colonic mucosa. Compounds passing the digestive system reaching the colon could potentially be detected in fecal water. We previously reported that intact fecal water samples from human volunteers significantly decreased prostaglandin production and COX-2 protein expression in colonic cells. The aim with the present study was to further study the composition of the fecal waters, using NMR spectroscopy and multivariate data analysis, and to trace the COX-2 inhibiting activity. Intact fecal water samples and fractions thereof were analyzed for their ability to inhibit prostaglandin E2 production in the human colon cell line HT-29. The majority of the tested aqueous phases derived from intact fecal water showed ability to inhibit prostaglandin production in cells (13.8±1.34% inhibition, p=0.01). NMR analysis indicated the presence of significant quantities of amino acids and fatty acids. Major metabolites included; acetic acid, butanoic acid, propanoic acid, glutamic acid and alanine. Smaller amounts of glycine and fumaric acid, which are known to have anti-inflammatory and anti-tumorigenic properties, were also detected. This study describes for the first time NMR metabolomic analysis of fecal water from subjects on a vegetarian diet.